Assessing Impact of Development Scenarios on the Social Cost of Energy Consumption in Industry in Isfahan Province using a System Dynamics Approach - Hossein Abolghassemzadeh; Elnaz Zekri; Banafsheh Zahraie; Mohsen Nasseri (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Greenhouse gas emissions and air pollutants are major challenges facing humanity today, mainly due to the consumption of energy sources. Industry makes an important contribution to the development of a country, but also contributes to increased energy consumption, which is unavoidable. To address this issue, the use of energy and emissions modeling can be very helpful in understanding the processes involved in reducing energy consumption, identifying emissions patterns and assessing the social costs associated with these emissions. Methods: In this study, a systemic dynamics model was developed to calculate greenhouse gas emissions and air pollutants in the industrial sector of Isfahan province. The model considers industrial energy consumption for the years 2011-2020 and estimates the social costs associated with these emissions. Various development scenarios were applied to the model and the reduction in social costs was calculated. Results: The social costs associated with greenhouse gas emissions and air pollutants were between 2.58 and 3.79 million dollars (based on 2002 USD). The highest social costs occurred in 2012and the lowest in 2014. Carbon dioxide was found to be the largest contributor to these social costs. Conclusion: Mazut fuel and the resulting greenhouse gas emissions are the main contributors to social costs in the study area, and industry and power plants are known to be the main consumers of this fuel. Therefore, the scenario in which mazut fuel is banned from industry has the greatest impact on reducing social costs. Furthermore, despite the higher efficiency of combined cycle power plants compared to gas-fired power plants, the scenario of converting gas-fired power plants into combined cycle power plants is recognized as the last proposed scenario to reduce social costs.